2022
DOI: 10.5551/jat.62832
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Education Program for the Japan Diet on Cholesterol Efflux Capacity: A Randomized Controlled Trial

Abstract: Improving cholesterol efflux capacity (CEC) of high-density lipoprotein (HDL) has been regarded as a novel target for preventing cardiovascular disease. HDL reportedly has antioxidant properties which may contribute to its functions. We investigated changes in CEC with intake of the Japan Diet (JD) recommended by the Japan Atherosclerosis Society and the relationship of these changes to serum antioxidant concentrations.Methods: A randomized parallel controlled clinical trial on JD intake was performed in Japan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…Blood was collected in the morning following a 12-hour fast and serum samples were obtained and stored at −80 ℃ until analyses. The data on total cholesterol (TC), LDL-C, high density lipoproteincholesterol (HDL-C), TG, malondialdehyde-modified low-density lipoprotein (MDA-LDL), oxygen radical absorbance capacity (ORAC), high-molecular-weight (HMW) adiponectin and leptin, and the measurement methods for each were described in our previous report in detail 13,14) and were also used in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Blood was collected in the morning following a 12-hour fast and serum samples were obtained and stored at −80 ℃ until analyses. The data on total cholesterol (TC), LDL-C, high density lipoproteincholesterol (HDL-C), TG, malondialdehyde-modified low-density lipoprotein (MDA-LDL), oxygen radical absorbance capacity (ORAC), high-molecular-weight (HMW) adiponectin and leptin, and the measurement methods for each were described in our previous report in detail 13,14) and were also used in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that lifestyle interventions generally yield small changes in cardiovascular risk factors [29][30][31] and few changes in the incidence and mortality resulting from a cardiovascular disease or total mortality in general populations [31][32][33] . The combination of lifestyle and medical interventions yielded larger effects on cardiovascular disease or total mortality.…”
Section: Advance Publication Journal Of Atherosclerosis and Thrombosismentioning
confidence: 99%